2003
DOI: 10.1046/j.0305-1846.2003.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic cerebrospinal fluid absorption pathways in neonatal sheep revealed by subarachnoid injection of Microfil

Abstract: There is mounting evidence that a significant portion of cerebrospinal fluid drainage is associated with transport along cranial and spinal nerves with absorption taking place into lymphatic vessels external to the central nervous system. To characterize these pathways further, yellow Microfil was infused into the cisterna magna of 2-7-day-old lambs post mortem to perfuse either the cranial or spinal subarachnoid compartments. In some animals, blue Microfil was perfused into the carotid arteries simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 33 publications
4
64
0
Order By: Relevance
“…Some of the smaller cervical lymphatics that we may not have identified could have delivered tracer into the bloodstream by anastomosing independently with the veins in the neck. Additionally, in previous sheep studies, we identified afferent vessels upstream of our point of cervical vessel cannulation that anastomosed consistently with a local vein (Zakharov et al, 2003.). These vessels would deliver the 125 I-BSA directly into the bloodstream and would be accounted for in the vascular recovery portion of total recovered tracer.…”
Section: Limitations and Assumptionsmentioning
confidence: 99%
“…Some of the smaller cervical lymphatics that we may not have identified could have delivered tracer into the bloodstream by anastomosing independently with the veins in the neck. Additionally, in previous sheep studies, we identified afferent vessels upstream of our point of cervical vessel cannulation that anastomosed consistently with a local vein (Zakharov et al, 2003.). These vessels would deliver the 125 I-BSA directly into the bloodstream and would be accounted for in the vascular recovery portion of total recovered tracer.…”
Section: Limitations and Assumptionsmentioning
confidence: 99%
“…The correlation of a non-physiological CSF composition and fluid dynamics has been recently shown in patients with degenerative neurological disorders (Rubenstein 1998;Silverberg et al 2003). In addition to CSF resorption in arachnoid villi, the concept of CSF drainage through the lymphatics has been shown in animal experiments (Boulton et al 1998a(Boulton et al ,b,1999Johnston 2000Johnston ,2003Johnston and Papaiconomou 2002;Zakharov et al 2003;Lüdemann et al 2005).…”
mentioning
confidence: 99%
“…In addition, they suggest that additional mechanical damage (e.g. elevated local pressure) as well as biochemical injury through an accumulation of biologically active molecules may contribute to disease progression and tissue damage to blood vessels, axons and neurons (Link and Olsson, 1972;Logdberg and Wester, 2000;Urade and Hayaishi, 2000;Reiber, 2001;Fujitani et al, 2002;Taniike et al, 2002;Ragolia et al, 2003;Zakharov et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery of lymphatic vessels in the dura of the human ON-and their ability to drain CSF as demonstrated with a marker substance-may offer a CSF outflow route from the perioptic space (Killer et al, 1999(Killer et al, , 2003. The results of experimental studies in animals describe CSF drainage into lymphatic vessels (Boulton et al, 1998;Johnston, 2000Johnston, , 2003Zakharov et al, 2003). In cats CSF outflow from cisternal infusion to the distal portion of the ON has been demonstrated (Lüdemann et al, 2005).…”
Section: Introductionmentioning
confidence: 99%